Water Treatment Stage Impacts on the Occurrence of Bacteriological Indicators and their Multiple Antibiotic Resistance Index - Mudau, Khuthadzo Lunsford; Ntobeng, Lesoka Reneileo; Kalu, Chimdi Mang; Khumbudzo, Maphangwa; Masindi, Vhahangwele; Tekere, Memory (Engineering, Technology & Applied Science Research, 2024)
Constant monitoring of the bacteriological indicators of drinking water and the associated Multiple Antibiotic Resistance (MAR) index as impacted by seasonal variations and different stages of Drinking Water Treatment Plants (DWTPs) may assist in understanding the pattern of their seasonal occurrences and the regular operations of the treatment plant that influence their removal. In this paper, the impact of the seasons and of the different stages of DWTPs on bacteriological indicator occurrence and the MAR-index of five treatment plants from three provinces in South Africa were assessed. Colilert-18 and Enterolert Quanti-Tray/2000 IDEXX methods were used to enumerate total coliform, E. coli, and Enterococcus spp. of water samples from the different treatment stages. Kirby–Bauer disc diffusion technique was used to assess the antibiotic susceptibility of the indicator bacteria isolates. All the measured physicochemical parameters were within the permissible limits. All the treatment plants essentially had a very high reduction of the indicator bacteria across all seasons. However, only two plants maintained the microbiological quality of the final treated water in compliance with the standards. A total of 121 isolates were obtained, and 106 isolates were multidrug resistant with the greatest resistance recorded for the Beta-lactams class of antibiotics. The MAR-index varied across seasons and with different plants. This implied that the usage of antibiotics is season- and site-dependent. The different stages of treatment reduced the indicator bacteria with the most reduction occurring in disinfection and candy stages. These findings extend the knowledge of how the treatment stages and seasons shape indicator bacteria and antibiotic resistance in drinking water.